Strengthening Religious Values through Character Education among Students of Muhammadiyah 2 Junior High School Karanganyar and State Junior High School 2 Tasikmadu, Karanganyar - Tarno; Sukari (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study employs a character education–based approach to examine the strengthening of religious values among junior high school students at Muhammadiyah 2 Junior High School Karanganyar and State Junior High School 2 Tasikmadu Karanganyar. The main objective of this research is to analyze the effectiveness of character education in reinforcing students’ religious values, particularly in terms of religious attitudes, daily behavior, and moral awareness. This research adopts a quantitative descriptive method with a survey design. The research sample consisted of 30 students, selected using a purposive sampling technique. Data were collected through questionnaires measuring students’ religious values before and after the implementation of character education–based learning activities. The data were analyzed using descriptive statistical techniques in the form of percentages. The results show that the implementation of character education significantly contributed to the strengthening of students’ religious values. The findings indicate that 86.7% of students demonstrated an improvement in religious attitudes, 83.3% showed increased consistency in practicing religious behaviors, and 80.0% exhibited stronger moral responsibility in both school and social environments. Overall, 83.3% of the students experienced a positive strengthening of religious values, while 16.7% showed moderate improvement. These results suggest that character education plays a crucial role in reinforcing religious values among junior high school students in both Islamic and public school settings